Application of ATR-FTIR Spectroscopy for Analysis of Salt Stress in Brussels Sprouts - Su-Min Yun; Cheol-Soo Kim; Jeung-Joo Lee; Jung-Sung Chung (Metabolites)
Salt stress is one of the environmental stresses that significantly reduces crop productivity and quality worldwide. Methods to overcome salt stress include developing salt-resistant crops by inserting various resistance genes or to diagnosing and responding to the effects of salt stress at an early stage. In this study, we investigate the effects of salinity stress on growth, photosynthetic efficiency, and metabolic changes in Brussels sprouts (Brassica oleracea var. gemmifera). Fresh weight and leaf area decreased significantly with increasing NaCl concentration, indicating that salinity stress has a detrimental effect on plant growth. However, chlorophyll fluorescence parameters did not show significant changes, suggesting that photosynthetic efficiency was not significantly affected over 10 days. Fourier transform infrared (FTIR) spectroscopy revealed notable metabolic adjustments, especially in lipids, plastids, proteins, and carbohydrates, indicating biosynthesis of protective compounds such as anthocyanins and proline in response to salinity stress. Pearson correlation analysis confirmed a strong relationship between NaCl concentration and the observed physiological and metabolic changes. The findings highlight the potential of FTIR spectroscopy as a non-destructive tool for early detection of salinity stress and timely intervention to improve crop resilience and yield. This study highlights the widespread application of FTIR spectroscopy in agricultural research to manage abiotic stresses in crops.